The Decameron - Boccaccio, Giovanni, 1313-1375.; Usher, Jonathan; Waldman, Guido (New York : Oxford University Press, 1993)
Translation of the fourteenth-century work, which contains one hundred linked stories as told by ten young Florentine noble men and women while fleeing the Black Death of 1348.
Adult
Keywords: Plague -- Europe -- History -- Fiction; Storytelling -- Fiction; Plague -- Fiction; Storytelling -- Fiction; Allegories; Frame-stories.